Abscess Formation after Septic Arthritis in the Sternoclavicular Joint of Two Healthy Men - Jeppe Henriksen; Mariann Tang; Vibeke Hjortdal (Case Reports in Surgery)
Abscess formation after septic arthritis in the sternoclavicular joint is a rare phenomenon in healthy people without immune suppression, intravenous drug abuse, or diabetes. Here we report two cases with formation of abscess in two middle-aged men, with no relevant comorbidities and no obvious sites of infection. The abscesses were both treated surgically with debridement followed by negative pressure wound therapy and antibiotics. The cases differ in diagnostic procedures and delay of diagnosis and broach the issues of handling a rare disease.